Study on the qualitative analysis and quantification of secondary metabolites on leaves of Tinospora Cordifolia (Neem Giloy). - KRISHAN KUMAR,; SHILPA BHARGAVA, (International Journal of Pharma and Bio Sciences, 2019)
The present research work presents the systematic valuation of T. cordifolia for its medical efficacy. Tinospora cordifolia (NeemGiloy) belongs to the family menispermaceae. It is a large extensively spreading glabrous, dioecious, evergreen perennial climber plant. T.cordifolia is used for the treatment of hypoglycemic, antioxidant, general weakness, anemia,antiallergic.The aim of this study is to analyze secondary metabolites phytoconstituents of leaf powder of T.cordifolia, qualitatively as well as quantitatively. Phytochemical screening of leaf extract of T.cordifolia carried out with aqueous and alcoholic solvent . Phytochemical screening revealed the presence of phenol, Flavonoid, alkaloids, Saponin, glycosides, carbohydrate, protein and tannin. The quantitative studies revealed that leaves of T.codifolia possessed Alkaloids, Tannin, Saponin, cardiac glycoside and Flavonoid value was found to be 44.6%, 0.23%, 30.8%, 35%, and 36.1% respectively. The high level of primary metabolites in the sample reveals its nutritive value.These secondary metabolites could be responsible for the observed medicinal properties of T.cordifolia by traditional herbalists.